Perpustakaan Sebagai Jantung Pendidikan - Makmur Syukri; Sri Wahyuni (Tarbiatuna: Journal of Islamic Education Studies, 2024)
The role of libraries is very important in supporting teaching and learning activities and research. Through library materials available in the library, library users can obtain the information and knowledge needed to improve the quality of life and work. Therefore, it is necessary to know strategies for strengthening libraries, as well as modern and successful libraries in supporting learning. In utilizing developments in information technology, libraries use them to provide services to the community. A digital-based library that makes it easier for students to obtain information, learning resources that are expected to support the quality of the learning process, support assignment activities in independent learning. So, here it is necessary to see how modern libraries provide good services to the community.